Testosterone Therapy Differently Regulates the Anti- and Pro-Inflammatory Cytokines in the Plasma and Prostate of Rats Submitted to Chronic Ethanol Consumption (UChB) - Mendes, Leonardo Oiveira; Scarano, Wellerson Rodrigo [UNESP]; Rochel-Maia, Sabrina Santos; Fioruci-Fontaneli, Beatriz Aparecida; Almeida Chuffa, Luiz Gustavo [UNESP]; Martinez, Francisco Eduardo [UNESP] (Wiley-Blackwell, 2014)
ProblemEthanol consumption damages the prostate, and testosterone is known by anti-inflammatory role.Methods of StudyThe cytokines were investigated in the plasma and ventral prostate of UChB rats submitted or not to testosterone therapy by ELISA and Western blot, respectively. Additionally, inflammatory foci and mast cells were identified in the ventral prostate slides stained by hematoxylin and eosin and toluidine blue, respectively.ResultsInflammatory foci were found in the ethanol-treated animals and absent after testosterone therapy. Plasma levels of IL-6 and IL-10 were not changed while TNF alpha and TFG-beta 1 were increased in the animals submitted testosterone therapy. Regarding to ventral prostate, IL-6 did not alter, while IL-10, TNF alpha, and TFG-b1 were increased after testosterone therapy. Ethanol increases NFR2 in addition to high number of intact and degranulated mast cell which were reduced after testosterone therapy.ConclusionsSo, ethanol and testosterone differentially modulates the cytokines in the plasma and prostate.
Keywords: Cytokines; ethanol; prostate; testosterone